2007
DOI: 10.1016/j.jhsb.2007.02.009
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Biomechanical Study Comparing the Spiral Linking Technique Against the Pulvertaft Weave for Tendon Repair

Abstract: A new spiral linking technique for tendon repair in which one end of the tendon is spiralled around the other end has been developed. Using pig trotter extensor tendons, the Pulvertaft weave technique was compared with this new technique. Twenty-five repairs using each technique were tested by tensile loading with an Instron testing machine. The spiral linking technique matched the strength of Pulvertaft method: the mean peak loads were 102 and 105 N, respectively. The Pulvertaft weave was stiffer than the spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 10 publications
0
36
0
4
Order By: Relevance
“…7 This technique is similar to the loop-tendon method in that intratendinous surfaces are not exposed, and only epitendinous contact occurs with overlapping of the tendons. Although the mechanism of tendon healing has been extensively studied with respect to end-to-end repair 3,15 and the healing of free tendon grafts, 16 the healing of weaving or overlapping repair methods has rarely been addressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 This technique is similar to the loop-tendon method in that intratendinous surfaces are not exposed, and only epitendinous contact occurs with overlapping of the tendons. Although the mechanism of tendon healing has been extensively studied with respect to end-to-end repair 3,15 and the healing of free tendon grafts, 16 the healing of weaving or overlapping repair methods has rarely been addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have been performed on the mechanical strengths of end-to-end tendon repairs during the healing stage 5,6 and on time-zero tensile strengths of weaving or overlapping repairs, 1,2,7,8 to our knowledge, no studies have evaluated the mechanical strengths of repair during the early postoperative period. We hypothesized that changes in the mechanical strength of the loop-tendon method may differ from those of the end-weave method over the early postoperative period owing to the differences in terms of repaired tendon constructs and contact surfaces.…”
mentioning
confidence: 99%
“…To repeat the suture after a former trial is often not possible, and is weaker as a result of the existing damage to the tendon. Other approaches to this problems include that of Kulikov et al [7], who found that in a spiral-linking technique the tendons were stronger than those after the Pulvertaft weave technique, but the inconvenience was not solved.…”
Section: Discussionmentioning
confidence: 99%
“…This process can be enhanced with the addition of strain and it has been found that tendon fibroblasts, dermal fibroblasts and mesenchymal stem cells are all capable of selfassembling collagen in this manner to produce (Pulvertaft, 1956). (B) Spiral linking weave (Kulikov et al, 2007). (C) Loop weave (Crook et al, 2013).…”
Section: Tissue Engineering Of Grafts and Biomaterialsmentioning
confidence: 99%